Clinical Phenotypes of Malnutrition in Young Children: Differential Nutritional Correction - Irina A. Belyaeva; Elena P. Bombardirova; Evgeniia A. Prihodko; Andrey Yu. Kruglyakov; Anna A. Mikheeva; Arina R. Larina (Вопросы современной педиатрии, 2023)
This review article summarizes current data on malnutrition etiology and pathogenesis in infants. Topical requirements for revealing this condition, its diagnosis and severity assessment via centile metrics are presented. The characteristics of the most common clinical phenotypes of postnatal growth insufficiency in infants (premature infants with different degree of maturation, including patients with bronchopulmonary dysplasia) are described. Differential approaches for malnutrition nutritional correction in these children are presented. The final section of the article describes special nutritional needs for children with congenital heart defects in terms of hemodynamic disorders nature and severity. Modern nutritional strategies for preparation of these patients to surgery and for their postoperative period are presented. The use of high-calorie/high-protein product for malnutrition correction in the most vulnerable patients with described in this review phenotypes is worth noticing.